Kebertahanan Kosakata Bahasa Bajo dalam Bidang Kelautan pada Siswa Melalui Metode Project Based Learning (Kajian Ekolinguistik) - Paesani, Arham; Syamsuddin, Syamsuddin; Nur’aeni, Ida; Yunidar, Yunidar; Ulfah, Ulfah (ppjbsip, 2025)
This study aims to describe the level of marine vocabulary survival of Bajo language students at SMPN 7 Menui Satap, Morowali Regency, using the Project Based Learning (PBL) method and to identify the ecological and sociolinguistic factors that influence it. This study uses an ecolinguistic approach with a descriptive quantitative design. Data were collected through a vocabulary questionnaire involving 50 students with 100 marine vocabulary items, supported by interviews and documentation. Data analysis was conducted using percentage techniques and interpretive qualitative analysis. The results show that the level of marine vocabulary survival of Bajo language reached 80.72% and is in the category of still surviving. Vocabulary directly related to daily maritime activities shows a high level of survival, while rarely used traditional vocabulary is starting to weaken and is at risk of being lost. Vocabulary survival is influenced by natural factors, such as the condition of the marine environment and the geography of coastal areas, as well as social factors, such as the livelihood of fishermen and language use within the family. Conversely, the dominance of Indonesian in schools, the influence of social media, and the weakening of intergenerational transmission are the main factors in the decline of vocabulary survival. AbstrakPenelitian ini bertujuan mendeskripsikan tingkat kebertahanan kosakata bahasa Bajo dalam bidang kelautan pada siswa SMPN 7 Menui Satap Kabupaten Morowali melalui metode Project Based Learning (PBL) serta mengidentifikasi faktor-faktor ekologis dan sosiolinguistik yang memengaruhinya. Penelitian ini menggunakan pendekatan ekolinguistik dengan desain kuantitatif deskriptif. Data dikumpulkan melalui angket kosakata yang melibatkan 50 siswa dengan 100 kosakata kelautan, didukung wawancara dan dokumentasi. Analisis data dilakukan dengan teknik persentase dan analisis kualitatif interpretatif. Hasil penelitian menunjukkan bahwa tingkat kebertahanan kosakata bahasa Bajo bidang kelautan mencapai 80,72% dan berada pada kategori masih bertahan. Kosakata yang berkaitan langsung dengan aktivitas maritim sehari-hari menunjukkan tingkat kebertahanan tinggi, sementara kosakata tradisional yang jarang digunakan mulai mengalami pelemahan dan berpotensi hilang. Kebertahanan kosakata dipengaruhi oleh faktor alam, seperti kondisi lingkungan laut dan geografis wilayah pesisir, serta faktor sosial, seperti mata pencaharian nelayan dan penggunaan bahasa dalam keluarga. Sebaliknya, dominasi bahasa Indonesia di sekolah, pengaruh media sosial, dan melemahnya transmisi antargenerasi menjadi faktor utama penurunan kebertahanan kosakata.